Time dependency of fluid flow near the top of the core - Bhattacharyya, A. (My University, 1998)
Fluid flow in the core is assumed to consist of a slowly varying (on time scales > magnetic diffusion time) part and a smaller, rapidly varying part as in the theory of the hydromagnetic dynamo put forward by Braginsky (1965). On the basis of this theory, geomagnetic secular variation models for the last 150 years are used to determine a rapidly varying, axisymmetric, poloidal motion of the fluid near the top of the core as a function of latitude in regions away from the equator. Approximations made in estimating this motion fail near the equator, thus restricting the estimates to latitudes ≥40°. Amplitude of the oscillating part of the axisymmetric poloidal flow is found to be ≤1 km/yr in the northern hemisphere, and nearly 3 km/yr in some parts of the southern hemisphere. The nature of temporal variation of this component differs significantly between the northern and southern hemispheres during the period under consideration.
Keywords: Fluid flow; Bore-mantle boundary; Geomagnetic secular variation model; Geodynamo model